La potencia de Mistral y su imagen performativa. - GÁLVEZ, FRANCISCA (Nomadías)
Gabriela Mistral was the first and only Latin American woman to receive the Nobel Prize in Literature in 1945. Her image has been constructed around the roles of mother and teacher, framed within heteronormativity. Author Fiol Matta suggests that Mistral used her image as a mask to navigate her social and political context. From this perspective, the text will examine different dimensions of this public construction. Furthermore, Mistral's figure has been reinterpreted in recent decades, seen as a symbol of resistance and feminism with the arrival of new waves of feminism and gender-dissident communities. The essay analyzes how performativity and queerness manifest in Mistral's life and work. Mistral embodies an image of queerness that challenged the norms of her time and Chilean society. Her motherhood was non-reproductive, and her image as a celibate mother contrasts with her private life-issues exploited by the prevailing notion of motherhood at the time. On the other hand, Mistral's letters reveal her desires and sexuality, often silenced in her public persona. Mistral's performativity is understood as a process of repeating norms that allowed her to occupy positions of power.